Single-session radiofrequency ablation for the treatment of benign cystic thyroid nodules: A prospective study - Van Bang Nguyen; Trong Binh Le; Chi Le Van (PLoS ONE, 2026)
Background Benign cystic thyroid nodules are commonly encountered in clinical practice and often require intervention due to compressive symptoms or cosmetic concerns. While ethanol ablation (EA) has been widely used, radiofrequency ablation (RFA) has emerged as a promising alternative, particularly for nodules with a significant solid component. This study aimed to evaluate the short-term efficacy and safety of single-session RFA in treating purely cystic and predominantly cystic thyroid nodules (PCTNs). Methods This prospective study included 38 patients with benign cystic thyroid nodules (10 purely cystic and 28 PCTNs) treated with single-session RFA. Pre- and post-treatment evaluations were performed using ultrasound imaging and thyroid function tests at 1, 6, and 12 months. The primary endpoint was volume reduction rate (VRR), and therapeutic success was defined as VRR > 50%. Complications were assessed according to international image-guided tumor ablation criteria. This study was registered at ClinicalTrials.gov (identifier: NCT07115576). Results RFA resulted in significant volume reduction, with VRR improving from 65.97 ± 22.19% at 1 month to 83.29 ± 17.33% at 6 months and 82.49 ± 23.18% at 12 months (p = 0.004). Purely cystic nodules demonstrated higher VRR than PCTNs at all follow-up points (p < 0.05). Thyroid function remained stable post-procedure. The therapeutic success rate was 83.3% at 1 month and 86.7% at 12 months, with no major complications reported. Purely cystic nodules showed a consistently higher and more durable response than PCTNs. Conclusion Single-session RFA appears to be a safe and effective minimally invasive treatment option for large benign thyroid nodules, although confirmation in comparative studies is needed. The technique is particularly advantageous for purely cystic nodules and offers a minimally invasive alternative to surgery or multiple EA sessions. Trial registration ClinicalTrials.gov NCT07115576